2022
DOI: 10.1007/s11897-022-00575-w
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Frailty in Heart Failure: Is There a Biomarker Signature?

Abstract: Purpose of Review Sarcopenia and frailty are common in patients with heart failure (HF) and are strongly associated with prognosis. This review aims to examine promising biomarkers that can guide physicians in identifying sarcopenia and frailty in HF. Recent Findings Traditional biomarkers including C-reactive protein, aminotransaminase, myostatin, and urinary creatinine as well as novel biomarkers including microRNAs, suppression of tumorigenicity 2 (ST2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 130 publications
0
7
1
Order By: Relevance
“…Importantly, studies suggest that the levels of sST2 may also serve as a potential predictive biomarker for frailty in patients with HF and other critical illnesses. 45,46 However, we did not observe any association of sST2 with either physical performance parameters or overall frailty in patients with CHF. Hence, sST2 may contribute to disease severity due to its crucial role in inducing systemic inflammation but may not be a predictive biomarker of frailty in critically ill patients.…”
Section: Discussioncontrasting
confidence: 72%
“…Importantly, studies suggest that the levels of sST2 may also serve as a potential predictive biomarker for frailty in patients with HF and other critical illnesses. 45,46 However, we did not observe any association of sST2 with either physical performance parameters or overall frailty in patients with CHF. Hence, sST2 may contribute to disease severity due to its crucial role in inducing systemic inflammation but may not be a predictive biomarker of frailty in critically ill patients.…”
Section: Discussioncontrasting
confidence: 72%
“…Reduced HGS as a reflection of muscle wasting in patients with HF has been involved as an important component for both sarcopenia and physical frailty, which may at least partly explain the prognostic role of HGS in these patients 37 . Pathophysiologically, during the progression of HF, reduced cardiac output and systemic congestion lead to a reduction in food intake and exercise capacity, promote inflammatory responses, increase sympathetic excitability, lead to secretion changes of muscle‐related hormone, and finally result in muscular weakness 38 . Among them, the ubiquitin–proteasome system (UPS) could be activated by systemic inflammation and oxidative stress in HF, and result in autophagy and apoptosis, ultimately leading to skeletal muscle wasting 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that sarcopenia, which is primarily characterized by a progressive and widespread decline in skeletal muscle mass and muscle dysfunction, is common in patients with HF (about 10%) and is strongly related to the prognosis of HF ( 22 ). Also, loss of lean body mass was related to the occurrence of HF, particularly among older males ( 23 ).…”
Section: Discussionmentioning
confidence: 99%